1990
DOI: 10.1530/jrf.0.0890285
|View full text |Cite
|
Sign up to set email alerts
|

Influence of embryonic and maternal genotype on gestational events in the mouse

Abstract: Mice with high and low prenatal survival were used to study the influence of maternal and embryonic genotype on the timing of implantation, conceptus growth and gestation length. Mice selected for large litter size (Line S1) or rapid post-weaning weight gain (Line G) showed implantation was delayed and gestation prolonged in mice with low prenatal survival (Line G). Reciprocal transfer of Line-S1 and -G embryos to pseudopregnant recipients indicated that conceptus growth was influenced by maternal as well as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…In this study, embryonic and maternal genotype had an influence on implantation rate, with a higher number of embryos implanted from line A (embryonic genotype effect) and a higher number of embryos implanted in line R recipients (maternal genotype effect). Embryo genotype effect on survival at implantation concurs with previous studies (Barkley and Fitzgerald ; Youngs et al. ; Ernst et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, embryonic and maternal genotype had an influence on implantation rate, with a higher number of embryos implanted from line A (embryonic genotype effect) and a higher number of embryos implanted in line R recipients (maternal genotype effect). Embryo genotype effect on survival at implantation concurs with previous studies (Barkley and Fitzgerald ; Youngs et al. ; Ernst et al.…”
Section: Discussionsupporting
confidence: 92%
“…However, the influence of maternal and embryonic genotypes on placental weight is controversial. While both genotypes had an influence on foetal and placenta weight in mouse and pig (Al‐Murrani and Roberts ; Barkley and Fitzgerald ; Biensen et al. ; Wilson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the influence of embryonic and maternal genotypes on placental weight is controversial. While both genotypes had an influence on foetal and placenta weight in mouse and pig (Al‐Murrani and Roberts ; Barkley and Fitzgerald ; Biensen et al. ; Wilson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the influence of embryonic and maternal genotypes on placental weight is controversial. While both genotypes had an influence on foetal and placenta weight in mouse and pig (Al-Murrani and Roberts 1978;Barkley and Fitzgerald 1990;Biensen et al 1998;Wilson et al 1998), Moc e et al (2004a) stated that foetal weight in the last term of gestation depends on the maternal genotype, and foetal-placental weight depends on the embryonic genotype in rabbit. However, recently Vicente et al (2013) showed that embryonic genotype affects foetal weight, but both embryonic and maternal genotype affect foetal-placental weight in the last term of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…The advanced development of part of embryos in this case probaЬly was iпfluenced Ьу geнotype of tl1e donors. Such geнetical iнfluences are documeнted in mice (10).…”
Section: Resultsmentioning
confidence: 94%